Involvement of NADPH oxidase 1 in UVB-induced cell signaling and cytotoxicity in human keratinocytes - Glady, Azela (Biochem Biophys Rep, 2018)
Members of NADPH oxidase (Nox) enzyme family are important sources of reactive oxygen species (ROS) and are known to be involved in several physiological functions in response to various stimuli including UV irradiation. UVB-induced ROS have been associated with inflammation, cytotoxicity, cell death, or DNA damage in human keratinocytes. However, the source and the role of UVB-induced ROS remain undefined. Here, we show that Nox1 is involved in UVB-induced p38/MAPK activation and cytotoxicity via ROS generation in keratinocytes. Nox1 knockdown or inhibitor decreased UVB-induced ROS production in human keratinocytes. Nox1 knockdown impaired UVB-induced p38 activation, accompanied by reduced IL-6 levels and attenuated cell toxicity. Treatment of cells with N-acetyl-L-cysteine (NAC), a potent ROS scavenger, suppressed p38 activation as well as consequent IL-6 production and cytotoxicity in response to UVB exposure. p38 inhibitor also suppressed UVB-induced IL-6 production and cytotoxicity. Furthermore, the blockade of IL-6 production by IL-6 neutralizing antibody reduced UVB-induced cell toxicity. In vivo assay using wild-type mice, the intradermal injection of lysates from UVB-irradiated control cells, but not from UVB-irradiated Nox1 knockdown cells, induced inflammatory swelling and IL-6 production in the skin of ears. Moreover, administration of Nox1 inhibitor suppressed UVB-induced increase in IL-6 mRNA expression in mice skin. Collectively, these data suggest that Nox1-mediated ROS production is required for UVB-induced cytotoxicity and inflammation through p38 activation and inflammatory cytokine production, such as IL-6. Thus, our findings suggest Nox1 as a therapeutic target for cytotoxicity and inflammation in response to UVB exposure.